Isu Kontemporer Manajemen Sumber Daya Manusia dalam Pendidikan Islam - Fitri, Nurdina; Muamala, Siti; Patimah, Siti; Lughowi, Rifyal Ahmad (Universitas Pakuan, 2025)
CONTEMPORARY ISSUES OF HUMAN RESOURCE MANAGEMENT IN ISLAMIC EDUCATIONThis research aims to analyze contemporary issues in human resource management (HRM) in Islamic education and outlines the basic concepts of HRM from an Islamic perspective. The research aims to offer relevant and applicable solutions to Islamic educational institutions. Key issues discussed include the competency gap in the digital era, the mismatch between Islamic values and modern professional demands, and the limitations of conventional management systems. This qualitative study employed a literature review method. Findings indicate that addressing these challenges requires a strategic transformation in HRM in Islamic education. The solutions offered include Continuous Competency Development, Value Harmonization, and Technology Adoption.